Treatments for the early stage Hepatocellular Carcinoma: Laparoscopic Liver Resection or Percutaneous Radiofrequency, How to make the decision? - Jinli Zheng (Karger Publishers, 2021)
Hepatectomy is still as the first-line treatment for the early stage HCC, but the complication rate is higher than p-RFA and the overall survival rate is comparable in these two treatments. Therefore, the patients with small single nodular HCCs could get more benefit from p-RFA, and we need to do further research about p-RFA.